Isotope detection in molecules with ultrafast electron diffraction and rotational spectrometry. (1st May 2022) - Xiong, Yanwei; Zhao, Haoran; Saha, Sajib Kumar; Muvva, Sri Bhavya; Wilkin, Kyle J; Centurion, Martin
Abstract: Gas phase electron diffraction is a powerful technique to measure the structure of molecules in the gas phase, and time-resolved ultrafast electron diffraction has been successful in capturing structural dynamics taking place on femtosecond and picosecond time scales. Diffraction measurements, however, are not sensitive to isotope substitution, and thus cannot distinguish between isotopologues. Here we show that by impulsively aligning the molecules with a short laser pulse and observing the anisotropy in the diffraction signal over multiple revivals of the rotational wavepacket, the relative abundance of molecules with different isotopes can be determined. We demonstrate the technique experimentally and theoretically by studying the rotational dynamics of chloromethane with two naturally occurring chlorine isotopes 35 Cl and 37 Cl. We have determined the relative abundance and mass difference of the isotopes. This new methodology adds a new capability to the existing technique of ultrafast electron diffraction.